Exploration of Functional Properties and Applications of Probiotic Lactic Acid Bacteria in Fermented Milk Products: A Literature Review - Putri Dian Wulansari; Nurul Fransiska; Nurul Mukminah; Rifda Naufalin (Indonesian Journal of Food Technology, 2026)
Background: Probiotic lactic acid bacteria (LAB) in fermented milk products have attracted considerable attention due to their ability to offer diverse health benefits while simultaneously improving product quality. Comprehensive exploration of the functional properties and applications of probiotic LAB is still needed to meet the evolving demands of the dairy industry. Objective: This study aims to analyze and evaluate the functional properties, mechanisms of action, and applications of probiotic lactic acid bacteria in various fermented milk products through a comprehensive literature review approach. Methods: A structured literature review was conducted by collecting articles from Scopus, PubMed, and Google Scholar databases using keywords "probiotic lactic acid bacteria," "functional properties," and "fermented milk products" for publications between 2015–2025. From 120+ identified articles, 35 were selected based on inclusion criteria: (1) investigation of functional properties of probiotic LAB, (2) focus on fermented milk products, (3) clear methodology, and (4) full-text availability. Results: Probiotic LAB demonstrated antioxidant, immunomodulatory, antimicrobial, and hypocholesterolemic activities. Dominant applications were identified in yogurt, kefir, and other fermented milk products with significant improvements in viscosity, gel stability, and reduction of syneresis. Strains of Lactobacillus plantarum, Lactobacillus kefiranofaciens, and Streptococcus thermophilus exhibited the highest potential. Health benefits included enhanced intestinal mucosal immunity, prevention of chronic gastritis, and induction of IgA antibodies. Conclusion: Probiotic LAB show significant potential as biofunctional agents in the fermented milk industry with dual advantages (health and quality enhancement). However, further research is required on bioavailability, long-term storage stability, and viability at industrial production scales. Keyword: lactic acid bacteria, probiotics, functional properties, fermented milk, literature review